2021
DOI: 10.1308/rcsann.2020.0171
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology, prevalence, fracture site and management of maxillofacial trauma

Abstract: Introduction Maxillofacial fractures are often associated with severe morbidity, functional deficit, disfigurement and significant financial implications. The aim of this review was to investigate whether the aetiology, prevalence and management modalities of facial trauma can identify the common causes of facial trauma with a view to recommending measures to the appropriate governing bodies to change the current practice wherever possible. Methods The records of 1,112 patients referred to our oral and maxillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 26 publications
9
21
0
5
Order By: Relevance
“…Men are significantly more affected than women (Leporace and Paulesini Júnior 2009;Rashid et al 2013;Siwani et al 2014;Flandes et al 2019;Kanala et al 2021), which was confirmed by the present study, but in a lower ratio (3.5:1) than all other regions examined, including Brazil itself. There have been reports that the more severe the facial fracture the more likely it is that a man is involved (Horibe et al 2004).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Men are significantly more affected than women (Leporace and Paulesini Júnior 2009;Rashid et al 2013;Siwani et al 2014;Flandes et al 2019;Kanala et al 2021), which was confirmed by the present study, but in a lower ratio (3.5:1) than all other regions examined, including Brazil itself. There have been reports that the more severe the facial fracture the more likely it is that a man is involved (Horibe et al 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The most affected anatomical region (about half) in facial fractures is the mandible (Falcão and Leite Segundo 2005;Rashid et al 2013;Motamedi et al 2014;Liu et al 2020;Kanala et al 2021) followed by fractures of the middle third of the face, although in some studies this relationship is reversed but very close (Cabalag et al 2014;Abosadegh et al 2019), as in the present study (figure 4). The proportion of lower and upper jaw fractures was significantly lower compared to other studies, while the incidence of zygomatic and nasal fractures was significantly higher.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…A compreensão da frequência e distribuição de casos de fraturas faciais em uma população pode auxiliar no estabelecimento de prioridades de pesquisa para o tratamento e prevenção eficazes dessas lesões (KANALA et al, 2021) As fraturas faciais exigem especial atenção durante o diagnóstico por causa da proximidade anatômica do cérebro e da associação frequente com lesões concomitantes graves, como lesão cerebral traumática. As estruturas vitais na região da cabeça e pescoço devem, portanto, ser avaliadas sempre que houver suspeita de lesão na região maxilofacial (ABOSADEGH, RAHMAN & SADDKI, 2017).…”
Section: Introductionunclassified